ANALISIS FRAMING PEMBERITAAN ISU CHILDFREE PADA MEDIA ONLINE DETIK.COM (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
The focus of this research is to examine how Detik.com frames reporting related to the child-free issue during February 2023. Additionally, it aims to understand the bias in reporting the child-free issue on Detik.com online media. The type of research used is qualitative descriptive with a data management method of framing analysis. The framing analysis used in this study is based on Robert M. Entman's model, which includes four elements: define the problem, diagnose causes, make moral judgments, and treatment recommendations. The results of this study indicate that: 1) Detik.com's framing of the child-free issue emphasizes defining the problem by including responses from key figures related to the issue, such as the head of BKKBN and Vice President Ma'ruf Amin. The reporting aims to show disapproval of the childfree lifestyle choice. Detik.com provides strong reasons from various perspectives, including health and religious impacts. Additionally, Detik.com also offers solution recommendations for individuals who wish to delay having children or discuss with their partners. 2) Detik.com tends to provide reporting that is against the childfree lifestyle choice, involving figures like the head of BKKBN, Ma'ruf Amin, and Luqman Hakim highlighting the importance of having offspring in marriage. Out of the five news articles presented, most of them oppose childfree. Therefore, Detik.com's bias in reporting on the childfree issue is to provide responses that disagree with that choice. The implications of this research are that Detik.com and researchers share the same hope to improve the quality of reporting in online media. Detik.com is expected to continue committing to delivering messages clearly, providing necessary clarifications, and ensuring the presence of relevant and competent sources in every report. Meanwhile, researchers suggest that future studies be more selective in choosing significant and impactful news to provide more relevant and beneficial analysis, especially in the context of framing analysis in online media reporting. By focusing on news that has a significant impact on society, it is hoped that understanding and the quality of information presented can be enhanced.